Chemical Learning Module Based on Multiple Representations of Redox Materials - Gunawan, Nendi; Rahmawan, Setia (JTK (Jurnal Tadris Kimiya), 2023)
This study aims to create and evaluate the effectiveness of a chemistry learning module based on various redox material representations. Research and development (R&D) is the methodology used in this research: using a 4D model. It consists of defining, designing, developing, and disseminating stages. The research was carried out until the development phase. The quality of the module was assessed by material experts, media experts, and reviewers (chemistry educators). The respondents are 32 students in first grade of Senior High School Science class. Quality assessment and student responses were made using a Likert and Guttman scale questionnaire sheet. The result shows that the percentage of objectives found by validating all aspects of the module’s content by media, reviewers, and chemistry educators experts are 91.6%, 94.7%, and 81.25%, respectively, with excellent categories, and students responded positively to the module. The module is considered helpful as a learning media for redox topics.